Leadership and Teamwork in Building Organizational Employee Performance - Layly Dwi Rohmatunnisa' (CV. Inara, 2021)
Human resources are resources used to mobilize and synergize other resources to achieve organizational goals. Human capital management can be done through employee performance appraisal or performance appraisal. Employee performance appraisal is the process of planning, organizing, supervising, controlling and assessing performance. The role of superiors also affects employee performance. The leadership spirit possessed by superiors will also direct where employees will step towards organizational goals. In addition to the leadership spirit of superiors, another thing that has a role in employee performance is the work team (teamwork) in an organization. This study uses a type of qualitative descriptive research. The results of this study found that leadership is a cooperative